Buen Gusto and Classicism in the Visual Cultures of Latin America, 1780-1910 - Widdifield, Stacie G., 1953-; Niell, Paul B., 1976- (Book collections on Project MUSE., 2013)
"The promotion of classicism in the visual arts in late eighteenth and nineteenth-century Latin America and the need to "revive" buen gusto (good taste) are the themes of this collection of essays. The contributors provide new insights into neoclassicism and buen gusto as cultural, not just visual, phenomena in the late colonial and early national periods and promote new approaches to the study of Latin American art history and visual culture. The essays examine neoclassical visual culture from assorted perspectives. They consider how classicism was imposed, promoted, adapted, negotiated, and contested in myriad social, political, economic, cultural, and temporal situations. Case studies show such motivations as the desire to impose imperial authority, to fashion the nationalist self, and to form and maintain new social and cultural ideologies. The adaptation of classicism and buen gusto in the Americas was further shaped by local factors, including the realities of place and the influence of established visual and material traditions"--